Isolation and characterization of protein fractions isolated from camelina meal - Li, Ningbo; Qi, Guangyan; Sun, Xiuzhi S.; Wang, Donghai; Bean, Scott R.; Blackwell, Deidre (My University, 2014)
Camelina is a new oil crop in North America. Camelina meal, a by-product of the camelina oil extraction process, typically contains 10% to 15% residual oil and 40% crude protein. As camelina oil demand increases, utilization of camelina protein for value-added products is critical to food and biotechnology industries; however, few studies have been conducted on camelina proteins.In this study, camelina protein fractions (albumin, globulins, and glutelins) were isolated from camelina meal based on their solubility using three different sequences: method 0 (S0), method 1 (S1), and method 2 (S2). The proteins’ physicochemical properties, including solubility, amino acid profiles, molecular weight, and thermal and morphological properties, were also characterized. Results showed that S1 harvested more protein (88.20%) than S0 (84.05%) and S2 (76.52%). Glutelin was the major fraction (64.64%) in camelina, followed by globulin (17.67%), and albumin (10.54%). Essential amino acids accounted for approximately 40% of the total amino acids in camelina protein. High molecular weight aggregates stabilized by covalent bonds in the glutelin and albumin fractions, as shown in size-exclusion chromatography (SEC), are closely related to larger-size protein aggregates observed in TEM images.
Keywords: Albumin; Amino acid profiles; Camelina protein; FTIR; Globulin; Glutelin; Molecular weight; SEC; TEM; TGA